Islamic Values, Digital Marketing, and Purchase Intention: Their Impact on the Preservation of Local Wisdom in Halal MSMEs in Aceh - Diana; Mariana; Yudhy Widya Kusumo; Yeni Irawan; Rahmad; Muhammad Arifai (Journal of Islamic Economic and Business Research, 2025)
This study examines the role of integrating Islamic values and digital marketing strategies in enhancing Muslim consumers' purchase intention for halal-certified MSME products in Aceh and its impact on preserving local wisdom. Using a quantitative approach, the research employs an explanatory design, collecting data from 215 respondents through purposive sampling. Primary data is obtained through questionnaires, supported by secondary data for contextual analysis. The findings reveal that the application of Islamic values plays a fundamental role in shaping consumer purchase intentions, emphasizing the importance of ethical principles in influencing purchasing behavior. Digital marketing strategies also positively contribute to consumer interest, though their influence is smaller compared to Islamic values. Additionally, the study highlights a strong relationship between consumer purchase intentions and the preservation of local wisdom in Aceh. It underscores the importance of a balanced approach that integrates value-based strategies with digital promotion to maximize consumer interest while preserving local traditions. The research advocates for holistic marketing strategies that align with Islamic principles and cultural preservation efforts, enabling MSMEs to thrive and sustain Aceh’s heritage in the era of globalization.